ASSERTIVENESS AROUND THE 2019’s PRESIDENTIAL CANDIDACY DISCOURSE ON SOCIAL MEDIA: A SOCIOPRAGMATIC STUDY - Mahanani, Rista Yulisetya; Prayitno, Harun Joko; Ngalim, Abdul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This study aims to describe the form of assertiveness, speech continuity strategies, and social distancing scales in the discourse of the 2019’s presidential candidacy on social media (Instagram, Twitter, and Facebook). This research method uses a qualitative descriptive method. The data in this study are in the form of words, phrases, and sentences that contain assertiveness. The data sources in this study are Instagram, Twitter, and Facebook. Data collection used in this study is a note-taking method. The data analysis carried out in this study were the intralingual matching method, the PUP primary technique matching method, and the HBS advanced technique. The results of this study found that 1) the form of assertiveness in the discourse of the 2019’s presidential candidacy on social media, namely (a) the force to express a desire,(b) the force to brag about hatred, (c) the force to enhance politeness, (d) the force to report field facts, (e) the force to urge Pn's goals, (f) the force to raise complaints, and (g) the force to announce the agenda.2) continuity strategies in the form of (a) direct speech strategies and (b) indirect speech strategies. 3) the social distance scale contained in this study is (a) long-hedged speech and (b) short-hedged speech.